Missão como com-paixão : por uma teologia da missão em perspectiva latino-americana - Zwetsch, Roberto Ervino (2007)
The mercantile-missionary project that Spain and Portugal developed in Latin America at the end of the fifteenth century incorporated the native peoples within a colonialist System, submitting them to the Catholic faith and to the Empire, marked by the alliance between the cross and the sword, imposed new faith under the Catholic hegemony for more than three hundred years. Protestantism is continuously present as of the 19th century, also within the colonial system, but under the tutelage of new states, such as England, Holland and Denmark, and later the United States of America. After the evangelical immigrants, who constituted ethnic communities without missionary characteristics, the Protestantism of mission, coming from England and the United States of America, responded best to this new moment through missionary societies, interdenominational associations and missionary entities from different evangelical churches. With the consolidation of the evangelical presence by the end of the 19th century as an alternative to the Catholic religious hegemony, the coming of Pentecostalism in the beginning of the 20th century soon transformed this popular branch of Protestantism into the most dynamic sector. Based on this history, this dissertation debates the theology of the Protestant mission (or lack of it) and the ecumenical perspectives for Christian mission in the 21st century from the Latin American perspective. The method used was to study the theology of mission present in the works of four Protestant theologians, two of them from the Protestantism of mission, José Míguez Bonino and C. René Padilla; and the other two from the Protestantism of immigration, Valdir Steuernagel and Hermann Brandt. The first three are representatives of Latin American Protestantism and the last one is a representative of European theology that dialogs with Latin American theology. The author proposes as a missionary paradigm for the 21st century mission as com-passion, understood as a plural expression that denotes the compassionate action of God with humanity, through which he calls humanity to participate in his missio aimed at the kingdom of peace and justice. The church-in-mission participates in the missio Dei through the proclamation of the gospel, liberating service and evangelical solidarity. The dissertation seeks to demonstrate how mission is God s instrument for the liberation of the church through his Spirit which impels God s people to missionary action that is manifested as com-passion in following Christ for the transformation of the world.